Photodeposition of Copper and Chromia on Gallium Oxide: The Role of Co‐Catalysts in Photocatalytic Water Splitting. Issue 4 (3rd March 2014) - Busser, G. Wilma; Mei, Bastian; Pougin, Anna; Strunk, Jennifer; Gutkowski, Ramona; Schuhmann, Wolfgang; Willinger, Marc‐Georg; Schlögl, Robert; Muhler, Martin
<x xml:space="preserve">Abstract</x> Split second: The photocatalytic activity of gallium oxide (β‐Ga2O3) depends strongly on the co‐catalysts CuOx and chromia, which can be efficiently deposited in a stepwise manner by photoreduction of Cu2+ and CrO42−. The water‐splitting activity can be tuned by varying the Cu loading in the range 0.025–1.5 wt %, whereas the Cr loading is not affecting the rate as long as small amounts (such as 0.05 wt %) are present. Chromia is identified as highly efficient co‐catalyst in the presence of CuOx: it is essential for the oxidation of water.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>